Respiratory abnormalities among workers in an iron and steel foundry. Issue 2 (February 1985) - Johnson, A; Moira, C Y; MacLean, L; Atkins, E; Dybuncio, A; Cheng, F; Enarson, D
Abstract : A study of the health of 78 workers in an iron and steel foundry in Vancouver, British Columbia, was carried out and the results compared with those found in 372 railway repair yard workers who were not significantly exposed to air contaminants at work. The foundry workers were exposed to PepSet, which consists of diphenyl methane diisocyanate (MDI) and phenol formaldehyde and their decomposition products as well as to silica containing particulates. A questionnaire was administered by trained interviewers, and chest radiography, allergy skin tests, pulmonary function tests, and methacholine inhalation tests were carried out as well as measurement levels of dust and MDI. Compared with the controls, the foundry workers had more respiratory symptoms and a significantly lower mean FEV1 and FEF25-75% after adjustments had been made for differences in age, height, and smoking habit. Three workers (4.8%) had radiographic evidence of pneumoconiosis and 12 (18.2%) had asthma defined as presence of bronchial hyperreactivity, cough, and additional respiratory symptoms such as wheeze, chest tightness, or breathlessness. Sensitisation to MDI is probably the cause of asthma in these workers.